Values and Strategy Development and Management - P lyer, Ramu (Ushus Journal of Business Management, 2021)
This article highlights the values, vision, mission and socioeconomic objectives of few successful companies that have succeeded in the past, and that will succeed in the future also if they continue to stick to those values